One method for solution of the Cauchy problem for singular parabolic equations - Matiichuk , M. I. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We consider a system of parabolic type with singular coefficients on boundary hyperplanes. We reduce the solution of the Cauchy problem to an integral equation and determine the fundamental solution as the kernel of the inverse operator of the Cauchy problem.